1992
DOI: 10.1007/bf01400629
|View full text |Cite
|
Sign up to set email alerts
|

Does the shunt opening pressure influence the effect of shunt surgery in normal pressure hydrocephalus?

Abstract: Thirteen patients with normal pressure hydrocephalus were operated upon with an externally maneuverable shunt system (Sophy SU8) in order to investigate its influence on clinical outcome, intracranial pressure and cranial CT parameters. The opening pressure was set at high at surgery and lowered stepwise at intervals of three months to medium and low. The clinical condition, intracranial pressure and cranial CT parameters were examined at the end of the 3 months interval on each pressure level. The patients im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 48 publications
(6 reference statements)
1
17
0
1
Order By: Relevance
“…Although rare, sibling cases of NPH have been reported, in which the individuals had clinical features indistinguishable from iNPH. 8,26) More recently, a large family with NPH patients in three generations who had clinical and MRI features that were indistinguishable from iNPH has been reported. 29) It has also been suggested that a copy number variation in a certain region of the genome may play a role as a genetic risk factor for iNPH.…”
Section: -B Etiologymentioning
confidence: 99%
See 3 more Smart Citations
“…Although rare, sibling cases of NPH have been reported, in which the individuals had clinical features indistinguishable from iNPH. 8,26) More recently, a large family with NPH patients in three generations who had clinical and MRI features that were indistinguishable from iNPH has been reported. 29) It has also been suggested that a copy number variation in a certain region of the genome may play a role as a genetic risk factor for iNPH.…”
Section: -B Etiologymentioning
confidence: 99%
“…In recent studies that were strictly aimed at iNPH patients, the measurement of proteins and neuropeptides in the CSF has been conducted. Neurofilament light chain, 2,136) transforming growth factor (TGF)-b1, TGF-b type II receptor, and a2-leucine-rich glycoprotein (LRG) 84,85) are significantly increased in the CSF of iNPH patients, whereas acetylcholine esterase activity, lactic acid, 87) b-amyloid-42, 60,112) b trace, 26) a secreted form of b-amyloid precursor protein (APP), and a secreted form of APPa 112) were significantly decreased in the CSF of iNPH patients. Since the levels of total tau (t-tau), but not phosphorylated tau (p-tau), were increased in the CSF of iNPH patients, they were reported to be useful in the differential diagnosis of Alzheimer's disease.…”
Section: -C Csf and Serum Biochemical Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to this method, the initial pressure setting is determined based on the pressure environment of the upright condition in which shunt flow is expected to be a maximum and, therefore, the resultant pressure setting becomes relatively higher than previously considered. Evidence supporting this approach is available in several studies: One study showed improvement in symptoms in all subjects after setting the Sophy valve  (SV; Sophysa, U.S.A.) at a high pressure, 58) another study found that the final setting in more than 80% of patients with CHPV was approximately 150 mmH 2 O. 98B) If symptoms due to overdrainage develop in patients treated with conventional fixed-type valves, patients are advised to maintain a recumbent position and then allowed a gradual transition to the upright position.…”
Section: Postoperative Managementmentioning
confidence: 99%